A latent class analysis of friendship network types and their predictors in the second half of life - Gabrian, Martina; Huxhold, Oliver; Stevens, Nan L. (The journals of gerontology. Series B, Psychological sciences, social sciences, 2013)
Friendships contribute uniquely to well-being in (late) adulthood. However, studies on friendship often ignore interindividual differences in friendship patterns. The aim of this study was to investigate such differences including their predictors.The study builds on Matthews’s qualitative model of friendship styles. Matthews distinguished 3 approaches to friendship differing by number of friends, duration of friendships, and emotional closeness. We used latent class analysis to identify friendship network types in a sample of middle-aged and older adults aged 40-85 years (N = 1,876). Data came from the German Aging Survey (DEAS).Our analysis revealed 4 distinct friendship network types that were in high congruence with Matthews’s typology. We identified these as a discerning style, which focuses on few close relationships, an independent style, which refrains from close engagements, and 2 acquisitive styles that both acquire new friends across their whole life course but differ regarding the emotional closeness of their friendships. Socioeconomic status, gender, health, and network-disturbing and network-sustaining variables predicted affiliations with network types.We argue that future studies should consider a holistic view of friendships in order to better understand the association between friendships and well-being in the second half of life.